The effect of pretreatment of zerumbone on fatty liver following ethanol induced Hepatotoxicity - Fakurazi, Sharida; Ithnin, Hairuszah; Ganabadi, Shanti; J., Mohd Lip (Asian Network for Scientific Information, 2008)

(untitled)
This study was designed to determine whether zerumbone, an essential bioactive compound isolated from Zingiber zerumbet Smith protects against early ethanol induced liver injury in rats. Male Sprague-Dawley rats were administered with 0.05% (v/v) to 0.5% (v/v) of zerumbone for 14 days. Following the final dosage of zerumbone, the animals were administered with 50% (v/v) ethanol for 14 days. We have observed that pre-treatment of zerumbone had suppressed fatty liver formation following ethanol 50% (v/v) administration. Meanwhile, rats that were treated with ethanol only, found to show significant level of focal vacuolated fatty liver with focal necrosis in the mid zonal region. Therefore, fatty liver development was found to be extensively reduced in animals that were pretreated with zerumbone.